Design, fabricate and testing small rocket motor - Mohamad Izwan, Ghazali (2012)
There was a lot of study on Solid Rocket Motor (SRM) based solid propellant. This project focus on and discusses the study of optimum design based SRM characteristics including the methods of the optimum design selection and fabrication, analysis using COSMOS and static thrust testing. Before that, the researcher has focus on the fundamental of solid rocket motor for designing and fabricating. There are two main factors need to be considered in the design selection and fabrication which are performance or processability and mechanical strength. The theoretical performance of the propellant was obtained by using CHEM program. Together with literature study and theoretical performance, three models or design of nozzle with different size throat were finalized with consideration of the mechanical and processability factors. The propellant was a mixture of Potassium nitrate and sucrose. The rocket motors were manufactured or fabricated using lathe and milling machine. Then three solid rocket motors were tested to get the thrust and performance. The results show that the increasing of thrust and combustion pressure lead to the decreasing the throat size and increasing the throat length. The highest thrust was 1260N and burning time about 4 Sec. Meanwhile, for the performance characteristics, the specific impulse, Isp that obtained from static thrust testing for solid propellant was 4% lower than theoretically.